The Influence of Customer Trust and Value on Customer Loyalty Small and Medium Business (Smes) PT Bank Rakyat Indonesia Branch Office Cilegon - Hamdan Hamdan (Yayasan Ilomata, 2022)
Small and Medium Enterprises (SMEs) Customer Loyalty can be created through customer trust and value. In this study, specifically discusses the loyalty of Small and Medium Enterprises (SMEs) customers at PT. Bank Rakyat Indonesia Cilegon Branch Office. This study aims to determine the effect of two independent variables, namely the trust variable and customer value on the dependent variable, namely the loyalty variable of Small and Medium Enterprises (SMEs). The method of data collection in this study is to use a questionnaire, observation and documentation. The number of samples in this study was 1 00 respondents. Then an analysis was carried out on the data that had been obtained using the quantitative analysis method. The results of the study show that trust has a positive influence on the loyalty of Small and Medium Enterprises (SMEs) customers and customer value also has a positive influence on the loyalty of Small and Medium Enterprises (SMEs). positive on the loyalty of Small and Medium Enterprises (SMEs) customers of PT Bank Rakyat Indonesia Cilegon Branch Office